OPTIMIZATION OF SHADE PRINT HANDLING IN MANDIRI'S TEACHING BROCHURE REVIEW FROM THE PRINTING PROCESS AT OKA PRINTING COMPANY - Juwairiah Juwairiah (Politeknik Negeri Media Kreatif, 2022)
The printing process in principle is a stage of transferring ink from the printing reference to the printed material with a certain printing speed and pressure. This study discusses the brochure printing process, the causes of ghosted prints, and how to handle the shaded prints. Oka Printing is a company engaged in the printing sector, where the production results produce quality prints in the form of printed products. One of the printed results in the form of this brochure is a tangible proof of the Oka Printing Company to produce a quality printed product.Data collection techniques in this study were carried out in several ways, namely interviews or discussions in the field with parties related to the company, direct observations in the field and collecting references that helped in the preparation of this research. From the observations, it was found how the brochure printing process with a 4-color GTO 52 offset printing machine, the causes of ghosting, and how to handle ghosting.